Description of a new species from the tropical region—Mallomonas ricata sp. nov. (Chrysophyceae, Synurales) - Ignatenko, Marina E.; Huan, Phan Trong; Gusev, Evgeniy S. (Phytotaxa, 2026)
A new species Mallomonas ricata sp. nov. is described from Dak Lua swamp in Cat Tien National Park, Dong Nai Province, Vietnam. The species description is based on scale morphology studied using scanning and transmission electron microscopy. Mallomonas ricata sp. nov. belongs in section Planae, and similar to taxa from the Mallomonas matvienkoae / Mallomonas pseudomatvienkoae species complex. The main distinctive features of the new species are the presence of a wide hooded posterior rim and the large scales. This species was found in only one habitat.